Poor social distancing attitudes and practices may drive community transmission of COVID-19 – A Knowledge Attitude Practice study among the general population of Odisha, India - Sahoo, Jyotiranjan; Panigrahi, Sandeep Kumar; Epari, Venkatarao (Indian Journal of Community Health, 2021)
Background: Knowledge, attitude, and practice of the community can determine progress from localized to community transmission of COVID-19 in India. Aims and Objectives: To assess the knowledge, attitude and practice levels of the general population during the early phase of COVID-19 pandemic. Materials and Methods: A rapid cross-sectional survey was conducted among hospital visitors of a lead tertiary care hospital. Realtime data collection from 223 respondents was done and analyzed using Stata 12.1 SE. Results: Mean age was 38.2 ±13.5 years, 68.2% were males, mean education was 12.1 ± 3.7 years and 45.3% were gainfully employed. Almost all had heard about CORONA (221, 99.1%). Adequate knowledge was present on: a) mode of spread (48.0%); b) preventive measures (70.9%). Television (77.1%), social media (60.5%) and WhatsApp (44.0%) were sources of information. Positive attitude was seen for: a) wearing a mask (83.9%); b) health-seeking (85%) on presenting with symptoms; c) Self-isolation or home-quarantine (20%). Adequate knowledge towards the mode of spread, symptoms and control measures or positive attitudes for health-seeking were found to positively translate into correct practices (p?0.001). Conclusion: Attitudes and practices of social distancing, self-isolation or home-quarantine were not adequate to prevent the epidemic progress in India.